Eco-terrorism: radical environmental and animal liberation movements - Liddick, Don (Praeger, 2006)
Criminality in the environmental and animal rights movements -- History and philosophy of radical environmentalism -- History and philosophy of the animal rights movement -- Animal rights criminality -- Criminality in the radical environmental movement -- Structure and modus operandi of radical movements -- A profile of eco-warriors and animal liberationists -- The future of eco-terrorism and animal liberation